Developing Work Motivation for Lecturers at Some Public Universities in Ho Chi Minh City, Vietnam - Dung, Nguyen Thi Thuy (European Scientific Journal, ESJ, 2020)
This article presents the results from an investigation of current practices in building work motivation for lecturers in three public universities in Ho Chi Minh City, Vietnam. The survey aims to clarify the current state of motivational development for lecturers in these universities, and to contribute as a reference to baseline for measures to enhance the work motivations for lecturers. The survey was conducted by a combination of in-depth interview and questionnaire of 224 lecturers in the three universities. The results showed that the management of these universities have taken appropriate motivating measures, which have direct effect to the individual lecturers, through their work and through the working environment. Among them, the direct measures (raising salaray and incentives; providing supplemental pay, benefits and services; trainning and professional development) are performed the best in three universities. Howerver, the working environment enhancement measures, which require time and appropriate investment, must receive the most attention in the future.